Comparison of Student Anxiety Levels in Facing CBT Exams Based on Gender - Wahyuni Dyah Parmasari; Nauval Hakim; Ayly Soekanto (Journal of Agromedicine and Medical Sciences, 2022)
Anxiety is assumed to be an unclear feeling, which causes worry, fear of everything that does not necessarily happen. This anxiety has a psychological impact on a person including it can affect learning achievement. Various studies related to anxiety theory state that gender affects the level of anxiety. Women are considered more prone to anxiety than men. In this study, researchers measured men's anxiety degrees compared to women when taking computer-based tests (CBT) during the pandemic. Exams with this method are suspected to be one of the triggers for anxiety in medical students. The purpose of this study was to compare the level of anxiety of students and female students in facing CBT at Wijaya Kusuma University Surabaya during the pandemic. This study used a cross-sectional approach with a total sampling technique. The total number of respondents was 60 people, 16 men and 44 women. Respondents' anxiety degrees were measured by a measurement scale of depression, anxiety, and stress or what is known as the Depression Anxiety and Stress Scale 21 (DASS-21). The results showed that 12.5% of men and 31.8% of women were in the heavy and very heavy group. The conclusion of this study is that the level of anxiety of women is higher than those men. Keywords: anxiety levels, medical students, gender, computer based test exam